Conjugacy of Morse Functions on Surfaces with Values on a Straight Line and Circle - Prishlyak, O. O. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the conjugacy of Morse functions on closed surfaces. By using cellular decompositions of surfaces, we formulate a criterion for the conjugacy of Morse functions. We establish a criterion for the conjugacy of mappings into a circle with nondegenerate critical points.